Gerakan Masyarakat Cerdas Obat (GMCO): Upaya Pencegahan Self-Medication yang Tidak Rasional di Kalangan Masyarakat Kota Medan - Fauzi, Ziza Putri Aisyia; Puteri, Cut Intan Annisa (Universitas Mataram, 2025)
Self-medication is a common practice in the community, but it is high risk if done irrationally. Medan City as a big city with easy access to over-the-counter drugs faces challenges in increasing public literacy about the correct use of drugs. This community service program aims to improve public knowledge and attitudes towards self-medication through a community-based educational approach. The activity was carried out in the form of the Smart Drug Community Movement (GMCO) with interactive lecture methods, discussions, leaflet distribution, and pre-post tests at Sanggar Sungai Deli, Sei Mati Village, Medan Maimun District, Medan City. The evaluation results showed a significant increase in knowledge scores and changes in public attitudes towards drug use. GMCO can be a model of community pharmacy education that is worthy of being developed more widely in urban areas.